Diverting Ileostomy in Children With Functional Constipation: A Study Evaluating the Utility of Colon Manometry. Issue 5 (28th July 2022) - Rodriguez, Leonel; Colliard, Kitzia; Nurko, Samuel; Flores, Alejandro; Buchmiller, Terry L.
Abstract : Objectives: Pediatric functional constipation (FC) may require invasive evaluations [like colon manometry (CM)] and surgical interventions [including diverting ostomy (DO)]. We evaluated the utility of CM in guiding surgery after DO. Methods: Children with medically refractory FC undergoing an ostomy were included. Institutional Review Board approval was obtained for this retrospective study. Demographics and CM variables [high amplitude propagating contractions (HAPCs)] were recorded. Outcome measures: response to ostomy closure defined as successful if no need for further surgery after ostomy closure, and improvement on baseline CM after ostomy. A CM-guided ostomy closure algorithm was developed based on previous studies. We evaluated the association between response to ostomy closure and demographics, ostomy indication and CM improvement, and evaluated the role of CM predicting response using algorithm. Results: A total of 60 children underwent ostomy for FC (median age: 7.1 years, range 0.15–23.6 years, 50% female). Ostomy was closed in 30 patients and deemed successful in 23 of 30. CM was performed in 42 of 60 patients before ostomy and in 29 of 30 before ostomy closure. We found no association between ostomy outcome and age, gender, weight, imaging studies, follow-up time, time with ostomy, HAPCs, and CM improvement. We found an association between failed response and ostomy indication of antegrade colonic enemas (ACE) failure ( P = 0.026) and successful response when ostomy closure was guided by algorithm ( P = 0.03). Conclusions: DO is a useful intervention in selected children with medically refractory FC, improving colon motility in most. CM can successfully guide the timing and type of ostomy closure. Larger studies are needed to further validate our findings.